Застосування Базель III як запорука підвищення фінансової стійкості банківських установ - Сиром'ятникова, Оксана Валеріївна; Іванова, Юлія Олексіївна (НТУ "ХПІ", 2015)
Узагальнено нові вимоги Базельського комітету з питань банківського нагляду (Базель ІІІ) щодо капіталу та ліквідності та їх відмінність від попередньої редакції. Визначено основні напрями зростання капіталізації банків України з метою підвищення їх фінансової стійкості. Зроблено висновки щодо необхідності впровадження Базель ІІІ, дотримання вимог якого щодо обсягу і структури банківського капіталу та ліквідності, стане запорукою підвищення стійкості вітчизняних комерційних банків.

Basic requirements for the regulation of the banking system of Ukraine are generalized based on international standards of Basel III, which take into account a certain scale of commercial bank and assess the quality of its capital structure. Key aspects of the introduction of specialized financial instruments in the formation of capital to the requirements of Basel III by the gradual transition to domestic commercial banks. Main directions of growth of bank capitalization by Ukraine to improve their financial stability. The conclusions on the need for implementation of Basel III is subject to the requirements regarding the scope and structure of bank capital and liquidity will increase the stability of domestic commercial banks.
Application of Basel III as a guarantee of improving the financial stability of banks
Keywords: Базельський комітет; нагляд банківський; вимоги; капітал; ліквідність; requirements; capital